Design and Development of a New Electrically Small 3D UHF Spherical Antenna with 360° of Opening Angle in the Whole Space for RFID, WSN, and RSN Applications - Abdelhamid Bou-El-Harmel; Ali Benbassou; Jamal Belkadid (International Journal of Antennas and Propagation)
Several antenna designs have been made in order to obtain a novel electrically small 3D UHF spherical antenna (ka = 0.1916), which has a resonance frequency close to 915 MHz, produces a quasi-isotropic radiation with an opening angle equal to 360° in the whole space, and is used for RFID, WSN, and RSN applications. These antennas are based on different shapes and are wrapped on the Styrofoam sphere surface of dielectric constant close to air (ɛr=1.06). A T-match configuration is used to adapt the input impedance of antennas to a value of 50 Ω. The antennas form allows for placing the sensor electronics in its interior, to reconfigure it for numerous values of impedances and to operate it in other ISM bands by adjusting their geometric parameters.